2021
DOI: 10.1088/1755-1315/765/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on bioethanol production from rice straw and banana pseudostem through simultaneous saccharification and fermentation using Kluyveromyces marxianus

Abstract: To improve the efficiency of second-generation bioethanol production, simultaneous Saccharification and Fermentation (SSF) of top agricultural wastes in the Philippines such as rice straw and banana pseudostem was conducted using commercial enzymes and the thermotolerant yeast Kluyveromyces marxianus. Residues were initially subjected to chemical treatment prior to SSF. A constant inoculum loading of 10% vv -1 was introduced during SSF, and mixed with a nutrient supplemented solution. Aside from the enzyme loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…However, they used two pretreatment steps: acid pretreatment with 0.2 M H2SO4, followed by alkali pretreatment with 5% (w/v) NaOH, which probably resulted in higher costs and a longer production time. The ethanol concentration obtained in this research outperformed those of Gatdula et al (2021), who got 6.30 g/L and 5.35 g/L of ethanol from the SSF of rice straw and banana pseudostem by K. marxianus for 48 h, respectively. Our results were also better than those reported by Hemansi et al (2021), who found 20 g/L of ethanol during 24-72 h of SSF by K. marxianus using acid-alkali-pretreated cotton stalks.…”
Section: Simultaneous Saccharification and Fermentationmentioning
confidence: 61%
“…However, they used two pretreatment steps: acid pretreatment with 0.2 M H2SO4, followed by alkali pretreatment with 5% (w/v) NaOH, which probably resulted in higher costs and a longer production time. The ethanol concentration obtained in this research outperformed those of Gatdula et al (2021), who got 6.30 g/L and 5.35 g/L of ethanol from the SSF of rice straw and banana pseudostem by K. marxianus for 48 h, respectively. Our results were also better than those reported by Hemansi et al (2021), who found 20 g/L of ethanol during 24-72 h of SSF by K. marxianus using acid-alkali-pretreated cotton stalks.…”
Section: Simultaneous Saccharification and Fermentationmentioning
confidence: 61%